Impact strength elastomer composites based on polystyrene components separated from waste electrical and electronic equipment. Issue 5 (1st August 2019) - Grigorescu, Ramona M.; Ghioca, Paul; Iancu, Lorena; Grigore, Madalina E.; Ion, Rodica‐Mariana; Nicolae, Cristian‐Andi; Gabor, Raluca; Filipescu, Mircea I.; Rapa, Maria; Trusca, Roxana D.; Ghiurea, Marius
ABSTRACT: The reuse of plastic components of waste electrical and electronic equipment (WEEE) is an important concern both for environmental issues and to preserve the material resources, with minimum energy consumption. Considering that polystyrene fraction was reported as approximate 80% of the total amount of WEEE plastic, this article aims to evaluate the recycling of this fraction, without separation by components, by melt compounding with styrene‐butadiene block‐copolymer (SBS) and hydrogenated and maleinized SBS, the blend of the two elastomers acting both as an impact modifier and compatibilizer. The composites are characterized by mechanical analysis, impact tests, dynamic mechanical analysis, differential scanning calorimetry, thermogravimetric analysis, scanning electron microscopy, energy dispersive X‐ray analysis, and X‐ray diffraction. The recycling conditions of the polystyrene fraction as composites without eliminating the WEEE additives for improved UV and flame resistance, with physical mechanical properties comparable to those of high‐impact polystyrene resulted from the study. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48329. Abstract : Morphology of WEEE composites